A Typology and Analysis of Russian Universities’ Performance in Education and Research - Irina Abankina; Fuad Aleskerov; Veronika Belousova; Leonid Gokhberg; Kirill Zinkovsky; Sofya Kiselgof; Sergey Shvydun (Foresight and STI Governance)
Over the past decades due to increasing economic pressure and rising demands by government and society, the organizational landscape of higher education is changing while university activities become more diversified. The focus of public support is shifting from funding current activities of universities towards rewarding outcomes. There are, as a result, many strategies to adapt and develop universities in this changing environment. For example, emerging typologies for structuring a network of higher education institutions (HEIs) taking into account their diversity are at the forefront in many countries of agendas for greater efficiency in higher education. We advance a typology for HEIs in Russia taking into account indicators of research and teaching activities. We present an overview of best practices for HEIs, some typologies, a set of indicators and mathematical tools for constructing a typology of Russian public HEIs. This typology is based on clustering the input (resource allocation) and output (performance) indicators that characterize academic and educational achievements of HEIs. The proposed classification differentiates types of universities and contains a decision tree that allows assigning universities to one category or another. It can be used as a basis for a comprehensive analysis of diverse Russian universities and for government policies to address each of the identified HEI types, depending on their characteristics.